2012
DOI: 10.1186/1746-1596-7-60
|View full text |Cite
|
Sign up to set email alerts
|

A gene-protein assay for human epidermal growth factor receptor 2 (HER2): brightfield tricolor visualization of HER2 protein, the HER2 gene, and chromosome 17 centromere (CEN17) in formalin-fixed, paraffin-embedded breast cancer tissue sections

Abstract: BackgroundThe eligibility of breast cancer patients for human epidermal growth factor receptor 2 (HER2)-directed therapies is determined by the HER2 gene amplification and/or HER2 protein overexpression status of the breast tumor as determined by in situ hybridization (ISH) or immunohistochemistry (IHC), respectively. Our objective was to combine the US Food and Drug Administration (FDA)-approved HER2 & chromosome 17 centromere (CEN17) brightfield ISH (BISH) and HER2 IHC assays into a single automated HER2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…Hirschmann et al [18] reported the simultaneous analysis of HER2 gene and HER2 protein on a single slide in a small study with 25 gastric cancers, in which the same antibody and DISH probes from the current study were used but without naphthol phosphate. Recently, Nitta et al [12] described the diagnostic utility of the HER2 GPA technology in breast cancer, especially in equivocal cases or cases showing intratumoral heterogeneity of HER2. The present study is the first to evaluate the concordance of the HER2 statuses obtained using conventional methods (single IHC and DISH assays) and GPA in a large number of gastric cancer cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hirschmann et al [18] reported the simultaneous analysis of HER2 gene and HER2 protein on a single slide in a small study with 25 gastric cancers, in which the same antibody and DISH probes from the current study were used but without naphthol phosphate. Recently, Nitta et al [12] described the diagnostic utility of the HER2 GPA technology in breast cancer, especially in equivocal cases or cases showing intratumoral heterogeneity of HER2. The present study is the first to evaluate the concordance of the HER2 statuses obtained using conventional methods (single IHC and DISH assays) and GPA in a large number of gastric cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…HER2 immunohistochemistry, dual-color in situ hybridization, and gene-protein assay HER2 IHC, HER2 and chromosome 17 centromere (CEN17) DISH, and HER2 GPA assays were performed as previously described by Nitta et al [12]. Briefly, for HER2 IHC, HER2 protein expression was detected using the PATHWAY HER-2/neu rabbit monoclonal antibody (clone 4B5; Ventana Medical Systems, Inc., Tucson, AZ, USA) and the iVIEW DAB detection kit (Ventana) on a BenchMark XT automated slide staining system (Ventana).…”
Section: Cases and Tissue Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…PTs from all these subjects were characterized as either HER2-positive or Luminal B HER2-positive, as part of routine clinical assessment. From large-format paraffin blocks, several tissue cores were removed, sectioned, and stained using the HER2 tricolor Dual ISH DNA Probe Cocktail Assay, according to the standard protocol (Roche Diagnostics Scandinavia AB) (Nitta et al 2012). These tissue cores were selected based on their proximity to the original UM samples that were taken prior to fixation of the whole breast tissue (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…New tissue samples were taken from the immediate vicinity of these biopsy sites for morphological ERBB2/HER2 assessment. We applied this strategy in the combined analysis of ERBB2 expression and copy number analysis using the HER2 tricolor Dual ISH DNA Probe Cocktail Assay, allowing visualization of expression of the HER2 protein as well as the copy number variation of ERBB2 and the centromere of Chromosome 17 (Nitta et al 2012). Eleven cases from the Falun cohort were selected for this analysis, based on the results of ERBB2 analysis in UM samples from the Illumina platform.…”
Section: Aberration Load Of Ums and Their Distances From Pt(s)mentioning
confidence: 99%